Branched‐Chain Amino Acids and Mitochondrial Biogenesis: An Overview and Mechanistic Summary. Issue 20 (15th September 2022) - Hinkle, Jason S.; Rivera, Caroline N.; Vaughan, Roger A.
Abstract: Branched‐chain amino acids (BCAA) are essential in the diet and promote several vital cell responses which may have benefits for health and athletic performance, as well as disease prevention. While BCAA are well‐known for their ability to stimulate muscle protein synthesis, their effects on cell energetics are also becoming well‐documented, but these receive less attention. In this review, much of the current evidence demonstrating BCAA ability (as individual amino acids or as part of dietary mixtures) to alter regulators of cellular energetics with an emphasis on mitochondrial biogenesis and related signaling is highlighted. Several studies have shown, both in vitro and in vivo, that BCAA (either individual or as a mixture) may promote signaling associated with increased mitochondrial biogenesis including the upregulation of master regulator of mitochondrial biogenesis peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1α), as well as numerous downstream targets and related function. However, sparse data in humans and the difficulty of controlling variables associated with feeding studies leave the physiological relevance of these findings unclear. Future well‐controlled diet studies will be needed to assess if BCAA consumption is associated with increased mitochondrial biogenesis and improved metabolic outcomes in healthy and/or diseased human populations. Abstract : Branched‐chain amino acids (BCAA) may stimulate mitochondrial biogenesisvia activating mammalian/mechanistic target of rapamycin complex 1 (mTORC1), yin‐yang1 (YY1), peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha(PGC‐1α), endothelial nitric oxide synthase (eNOS), Sirtuin 1 (SIRT1), and AMP‐activatedprotein kinase (AMPK), as well as other targets. Such signaling may result from altered energetics and/or a need to increase mitochondrial enzymes thereby promoting BCAA catabolism.